1996
DOI: 10.1074/jbc.271.16.9526
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Synthesis in Mouse Embryos during Gastrulation and Craniofacial Development Linked to Class IV Alcohol Dehydrogenase Gene Expression

Abstract: Endogenous retinoic acid (RA) has been observed in vertebrate embryos as early as gastrulation, but the mechanism controlling spatiotemporal synthesis of this important regulatory molecule remains unknown. Some members of the alcohol dehydrogenase (ADH) family catalyze retinol oxidation, the rate-limiting step in RA synthesis. Here we have examined mouse embryos for the presence of endogenous RA and expression of ADH genes. RA was not detected in egg cylinder stage embryos but was detected in late primitive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 48 publications
7
111
0
1
Order By: Relevance
“…Some of the newly generated forms deserve further consideration. ADH4 has been assumed to be crucial in vertebrates for retinoic acid synthesis via retinol oxidation (Duester 1996). Retinoic acid is thought to be involved in the anterior/posterior axis formation in both ascidian and amphioxus and, also, in vertebrates (reviewed by Shimeld 1996).…”
Section: Functional Divergence and Evolutionary Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the newly generated forms deserve further consideration. ADH4 has been assumed to be crucial in vertebrates for retinoic acid synthesis via retinol oxidation (Duester 1996). Retinoic acid is thought to be involved in the anterior/posterior axis formation in both ascidian and amphioxus and, also, in vertebrates (reviewed by Shimeld 1996).…”
Section: Functional Divergence and Evolutionary Changesmentioning
confidence: 99%
“…Whereas a ubiquitous Adh3 expression has been shown in mouse and human (Giri et al 1989;Ang at al. 1996;Estonius et al 1996), a specific expression, restricted to the midgut region, has been shown in amphioxus by in situ hybridization (Cañestro et al 2000).…”
Section: Functional Divergence and Evolutionary Changesmentioning
confidence: 99%
“…In vitamin A de¢ciency, the forestomach shows hyperkeratosis and the number of goblet cells of the small intestine severely declines [13]. Because RA is involved in the epithelial cell di¡erentia-tion of the stomach and small intestine, and also because the endogenous RA levels in embryonic tissues are controlled by developmentally regulated mechanisms that are likely to include modulation of expression and/or activity of enzymes catalyzing RA synthesis [14,15], it was of interest to examine the developmental pattern of RALDH gene expression in these epithelial tissues. Further, we also studied the e¡ects of vitamin A status on RALDH gene expression in these tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures of ADH class I and class IV revealed a conserved active site that can accommodate long chain alcohols such as retinol [18][19][20]. ADH class I is expressed at high levels in many retinoid target tissues of embryos [15,21] and in adult epithelia, such as intestine, kidney, adrenal gland, testis, epididymis, uterus and ovary [15,[22][23][24][25]. Retinoid signaling is thought to function in an autocrine or paracrine fashion via the local production of RA at the site of action.…”
Section: Discussionmentioning
confidence: 99%